Eosinophilic gastroenteritis presenting as relapsing severe abdominal pain and enteropathy with protein loss. Issue 11 (21st October 2005) - Lin, H-H; Wu, C-H; Wu, L-S; Shyu, R-Y
Abstract : Eosinophilic gastroenteritis (EG) is an uncommon gastrointestinal tract disease, and diagnosis can be difficult. A combination of acute or recurrent abdominal pain with peripheral hypereosinophilia suggests the diagnosis. Surgery in patients with these features might therefore be avoided. Physicians must maintain a high index of suspicion and a working knowledge of the natural history of EG in order to establish the proper diagnosis. We present the case of a young man with EG who presented with relapsing severe abdominal pain and enteropathy with protein loss.